Canadian Problem Gambling Index (CPGI) prevalence studies [Canada]: Consolidated dataset ... - Ontario Problem Gambling Research Centre (Borealis, 2014)
The Canadian Problem Gambling Index (CPGI) originated in 2000 as a Canadian interprovincial research initiative to develop and validate a new measure to identify problem gamblers in population health surveys. Since the CPGI was introduced, all Canadian provinces and many jurisdictions in other countries have relied on this measure to estimate the prevalence of problem gambling in general and special populations. In 2007, the OPGRC carried out the process of soliciting researchers for data that were collected using the CPGI instrument in order to compile and harmonize data into one large dataset. This is a cross-national and cross sectional dataset (n=21,374) compiled from seven major prevalence studies of Canadian adults (18 or older) residing in the Canadian provinces. It includes 2191 variables with information on gambling activities, gambling behaviours, adverse consequences related to gambling, and problem gambling correlates. Selected variables were harmonized to facilitate cross national comparisons. ... : Type: Acknowledgements: Notes: This metadata relates exclusively to the OPGRC project to consolidate CPGI prevalence data from existing data sources. The following individuals and primary investigators deserve recognition for being instrumental in the release of this consolidated dataset: Ipsos-Reid, Gemini Research, Jackie Ferris, Harold Wynne, Garry Smith, David Patton, David Brown, Jaste Dhaliwal, Curt Pankratz, Brian Broszeit, Jamie Wiebe, Eric Single, Agata Falkowski-Ham, Phil Mun, Nadine Kaufman, Carolyn O’Keefe, and Heather Legg. It is also important to highlight the main funding sources for each of the contributing datasets used to create this consolidated dataset: Ministry of Public Safety and Solicitor General (British Columbia), Alberta Gaming Research Institute, Addictions Foundation of Manitoba, Canadian Centre on Substance Abuse, Responsible Gambling Council, and the Department of Health and Community Services (Newfoundland and Labrador).; ...